Social Media, Religious Extremism, and Ethical Responsibility in Nigeria: Balancing Free Speech and Moral Consequences. - Oyebanji Israel Temitope; Oyunwola Taiwo Olayinka; Ogunbiyi David Oluwabukunmi (Darul Yasin Al Sys, 2026)
This study examines the relationship between social media, religious extremism, and moral responsibility in Nigeria, with particular attention to the dual role of digital platforms as spaces for free expression and as channels for the dissemination of harmful ideologies. Against the backdrop of a communication landscape increasingly shaped by social media, the study addresses the rise of hate speech, misinformation, and the radicalization of vulnerable groups, especially within Nigeria’s context of deep ethnic and religious divisions and persistent security threats from extremist groups such as Boko Haram. The study seeks to explore how free expression can be protected while addressing the ethical consequences of digital communication and the underlying drivers of radicalization. Drawing on evidence from academic literature, policy texts, and illustrative case examples, the analysis shows that weak content moderation systems, legal and regulatory gaps, and enduring socio-economic grievances facilitate the spread of extremist narratives online. The study further highlights the roles of state institutions, technology companies, religious leaders, and the wider public in mitigating these risks. It concludes that unchecked online discourse can intensify extremist beliefs, fuel violence, and undermine social cohesion, thereby necessitating stronger multi-stakeholder cooperation to develop ethical, context-sensitive responses that safeguard democratic freedoms while promoting religious peace and national stability.